2010
DOI: 10.5713/ajas.2011.10091
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Chinese Indigenous Pig Breeds in Shandong Province Using Microsatellite Markers

Abstract: To investigate the genetic diversity of six Chinese indigenous pig breeds in Shandong province (Laiwu Black, Dapulian Black, Licha Black, Yantai Black, Yimeng Black and Wulian Black), explain their genetic relationship and assess their integrity and degree of admixture with three Western commercial breeds (Landrace, Yorkshire and Duroc), 303 individuals from these breeds were genotyped for 26 microsatellite markers. In general, high genetic diversity (observed heterozygosity ranging from 0.5495 to 0.7746) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
6
8
2
Order By: Relevance
“…Observed heterozygosity in most farms was higher than expected, and this was in agreement with only a few studies concerning eleven European pig breeds (Laval et al, 2000), six Chinese indigenous pig breeds (Wang et al, 2011) and the Guadyerbas pig breed (Rodrigáñez et al, 2008). According to Wang et al (2011), several factors such as non-random mating, Wahlund effect, sampling error, and the lower proportion of male individuals may cause deviation from Hardy-Weinberg equilibrium and higher H O than H E . Thus, although there were very few individuals of the Greek black pig and their geographical extension was quite limited, the genetic variation within farms was very high.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Observed heterozygosity in most farms was higher than expected, and this was in agreement with only a few studies concerning eleven European pig breeds (Laval et al, 2000), six Chinese indigenous pig breeds (Wang et al, 2011) and the Guadyerbas pig breed (Rodrigáñez et al, 2008). According to Wang et al (2011), several factors such as non-random mating, Wahlund effect, sampling error, and the lower proportion of male individuals may cause deviation from Hardy-Weinberg equilibrium and higher H O than H E . Thus, although there were very few individuals of the Greek black pig and their geographical extension was quite limited, the genetic variation within farms was very high.…”
Section: Discussionsupporting
confidence: 73%
“…However, the mean observed heterozygosity within farms in our study (H O = 0.712) was higher than any other corresponding values in similar studies, with this parameter ranging between 0.476 for the Taihu pig breed (Fan et al, 2002) and 0.686 for six Chinese indigenous pig breeds (Wang et al, 2011). Observed heterozygosity in most farms was higher than expected, and this was in agreement with only a few studies concerning eleven European pig breeds (Laval et al, 2000), six Chinese indigenous pig breeds (Wang et al, 2011) and the Guadyerbas pig breed (Rodrigáñez et al, 2008). According to Wang et al (2011), several factors such as non-random mating, Wahlund effect, sampling error, and the lower proportion of male individuals may cause deviation from Hardy-Weinberg equilibrium and higher H O than H E .…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Similar values were also reported by other studies. (Li et al, 2010;Li et al, 2015;Wang et al, 2004 andWang et al, 2011) Genetic bottleneck analysis: In a recently bottlenecked population, the observed gene diversity is higher than the expected equilibrium gene diversity because the allele numbers is reduced faster than the gene diversity which can be computed from the Na, under the assumption of a constant-size (equilibrium) population (Luikart et al, 1998a). In a population at mutation-drift equilibrium, there is approximately an equal probability that a locus shows gene diversity excess or a gene diversity deficit.…”
Section: F Estimatesmentioning
confidence: 99%
“…The papers published by Wang et al (2011), BerthoulySalazar et al (2012), Chen et al (2012) and Zaman et al (2013) contributed to the expansion of knowledge of isolated local breeds in Asia.…”
Section: Introductionmentioning
confidence: 99%